Are allergic multimorbidities and IgE polysensitization associated with the persistence or re‐occurrence of foetal type 2 signalling? The MeDALL hypothesis. Issue 9 (14th July 2015) - Bousquet, J.; Anto, J. M.; Wickman, M.; Keil, T.; Valenta, R.; Haahtela, T.; Lodrup Carlsen, K.; van Hage, M.; Akdis, C.; Bachert, C.; Akdis, M.; Auffray, C.; et al.
Abstract Allergic diseases [asthma, rhinitis and atopic dermatitis (AD)] are complex. They are associated with allergen‐specific IgE and nonallergic mechanisms that may coexist in the same patient. In addition, these diseases tend to cluster and patients present concomitant or consecutive diseases (multimorbidity). IgE sensitization should be considered as a quantitative trait. Important clinical and immunological differences exist between mono‐ and polysensitized subjects. Multimorbidities of allergic diseases share common causal mechanisms that are only partly IgE‐mediated. Persistence of allergic diseases over time is associated with multimorbidity and/or IgE polysensitization. The importance of the family history of allergy may decrease with age. This review puts forward the hypothesis that allergic multimorbidities and IgE polysensitization are associated and related to the persistence or re‐occurrence of foetal type 2 signalling. Asthma, rhinitis and AD are manifestations of a common systemic immune imbalance (mesodermal origin) with specific patterns of remodelling (ectodermal or endodermal origin). This study proposes a new classification of IgE‐mediated allergic diseases that allows the definition of novel phenotypes to (i) better understand genetic and epigenetic mechanisms, (ii) better stratify allergic preschool children for prognosis and (iii) propose novel strategies of treatment and prevention.